Reappraisal of Prevention of Crimes in Iran with Emphasis on Systemic Theory in Political Sciences - خلیل اله سردارنیا; میرزا مهدی سالاری شهر بابکی (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2019)
In the recent decades, Iran has been faced with this challenge too. The research question is that, by using of systemic formwork, what are the important approaches related to crimes pre-emption in Iran? The important crimes pre-emptive approaches consist of: boost of communicative and information approach between judicial system and society, civil associations, elites and citizens, boost of civil and informal control frameworks, serious using of socio-cultural control frameworks and new-institutional capability- building in judicial system as well as a serious willing to crime pre-emption and law sovereignty. The final conclusion of research is that, in spite of legal frameworks and new institutional capability building, yet the judicial system has not been complete successfulness in pre-emption of crimes. Earning of this aim entails using of mentioned communicative-systemic approaches and security and economics ones that needed another researches. This study has been conducted with analytic- theoric method and functional approach by using of systemic theory and model in pre-emption of crime.